INTERACTION BETWEEN DIFFERENT MOLECULAR FORMS OF IMMUNOGLOBULIN A AND RECOMBINANT DERIVATIVES POLYPEPTIDES OF BAC RECEPTOR PROTEINS FROM GROUP B STREPTOCOCCI - A. S. Korzhueva; D. G. Ibragimova; I. A. Ustinovich; Artem A. Totolian; M. P. Samoilovich; A. N. Suvorov (Медицинская иммунология, 2014)
Abstract. The article concerns interactions between immunoglobulin A and recombinant P6, P7, P8 polypeptides, designed on the basis of externally localized Bac protein of the Group B streptococci, possessing IgA-binding activity.There is a current demand for immunochemical reagents that are strictly specific for IgA, in order to develop antigenic standards for detection of IgA levels in biological fluids, as well as for affinity purification of IgA and its fragments.To analyze an opportunity of the abovementioned application ways for these proteins, a special study was performed to assay an interaction capability of recombinant P6, P7, P8 polypeptides binding to Fc regions of different IgA forms (serum IgA, secretory IgA, subclasses of serum IgA – IgA1, IgA2). Selectivity of ligand binding was specially confirmed.It was found out that, among three presented polypeptides, the structure of recombinant P6 derivative proved to be optimal for IgA-binding ability of Bac protein.Structural features of IgA-binding fragments of Bac protein, i.e., binding site position on the IgA molecule (proximity to epitopes for three monoclonal antibodies), variability of the site structure, as well as resistance of binding site for P6, P7, P8 in IgA molecule against partial disulfide bonds reduction. (Med. Immunol., vol. 10, N 4-5, pp 327-336).